9 Factors associated with the decision-making on endovascular thrombectomy for fhe management of acute ischemic stroke. (25th July 2019) - Goyal, M; Menon, B; Kashani, N; Wilson, A; Yoshimura, S; Campbell, B; Baxter, B; Rabinstein, A; Turjman, F; Fischer, U; Ospel, J; Kunz, W; et al.
Abstract : Background and purpose: Little is known about the real-life factors that clinicians use in selection of patients that would receive endovascular treatment (EVT) in the real world. We sought to determine patient, practitioner, and health system factors associated with therapeutic decisions around endovascular treatment. Methods: We conducted a multinational cross-sectional web-based study comprising of 607 clinicians and interventionalists from 38 countries who are directly involved acute stroke care. Participants were randomly allocated to 10 from a pool of 22 acute stroke case scenarios and stated how they would treat the patient A) under current local resources, and B) under assumed ideal conditions (i.e. without monetary or infrastructural constraints). Descriptive statistics and logistic regression was performed to determine multilevel factors associated with EVT, adherence to current EVT guidelines, and practice gaps between current local resources and assumed ideal conditions. Results: Of the 1330 invited participants, 607 (45.6%) participants completed the study (53.7% neurologists, 28.5% neuro-interventional radiologists, 17.8% other clinicians). NIHSS (34.9%), level of evidence (30.2%), ASPECTS or ischemic core volume (22.4%), patient's age (21.6%), and clinicians' experience in EVT use (19.3%) are the most important factors for EVT decision. Of all responses that met Class IA evidence for EVT, 86.8% were in favor of EVT. In case scenarios Class IIB evidence, 66.3% of responses favored EVT. Comparison between current and ideal practice settings revealed an overall practice gap of 4% (Class 1A evidence scenarios) and 3% (Class 2B evidence scenarios).EVT decision rates differed significantly between regions and specialties under current local resources (p <.001 respectively), but not under assumed ideal conditions (p =.563 and .397). Conclusions: In this large multinational survey, stroke severity, guideline-based level of evidence, baseline brain imaging, patients' age and physicians' experience were the most relevant factors for EVT decision-making. The high agreement between responses and Class I guideline recommendations and high EVT use even when guidelines were not available reflect the real-world acceptance of EVT as standard of care in patients with disabling acute ischemic stroke. The overall practice gap and the significant differences in EVT decision rates under current local resources suggest that physicians of different specialties and practicing in different geographic regions succumb to variable external restraints. Disclosures: M. Goyal: 1; C; This study was funded through an unrestricted Research Grant to the University of Calgary by Stryker Inc. 2; C; Medtronic, Stryker, Microvention, GE Healthcare, Mentice. B. Menon: None. N. Kashani: None. A. Wilson: None. S. Yoshimura: None. B. Campbell: None. B. Baxter: 2; C; Penumbra, Medtronic, Stryker, 880 Medical, Metactive. 4; C; Penumbra, viz.ai. 5; C; ownership interests on Route 92 and Marblehead. A. Rabinstein: None. F. Turjman: 2; C; consultant for Balt and Stryker. U. Fischer: 2; C; Medtronic, Stryker, CSL Behring. 6; C; Co-PI Swift direct trial (Medtronic). J. Ospel: None. W. Kunz: None. P. Mitchell: None. P. Sylaia: None. M. Cherian: None. B. Kim: None. J. Heo: None. A. Podlasek: None. M. Almekhlafi: None. M. Foss: None. A. Demchuk: None. M. Hill: None. G. Saposnik: 6; C; Gustavo Saposnik is supported by the Heart and Stroke Foundation of Canada Career Award.